Relation between carbon stocks, their stability and the bioactivity of humic substances from soils under integrated farming, livestock, and forestry - BALDOTTO, MARIHUS ALTOÉ; Baldotto, Lílian Estrela Borges (Revista Ceres, 2018)
Once it is stabilized in the soil, organic matter helps overcome limitations of Brazilian Oxisols, such as the cation exchange capacity, low nutrient availability, toxicity due to high aluminum content, and phosphate adsorption. Additionally, wet organic matter fractions are bioactive. It is, therefore, important to evaluate the biostimulant ability of compounds present in soil carbon stocks in order to develop sustainable technologies for tropical agriculture based on renewable natural resources. The aims of this study were to determine the redox potential of soil organic matter, measure soil carbon stock, evaluate the stability and bioactivity of isolated humic substances from integrated farm systems, livestock, and forests, and correlate them with other key soil attributes. The carbon stocks and their stabilities were determined from oxidation by dichromatometry and iodometry, respectively. Bioactivity was assessed using indicator corn plant yield data. The results indicated where native-like forests were reintroduced in lieu of pastureland, soil carbon stocks and their stability increased along with overall improvements in soil fertility, chemistry, physical properties, and biodiversity. The bioactivity of humic substances isolated from the soils used in integrated crop, livestock, and forestry management was higher than that of soils derived from pastures or eucalyptus stands.